The barriers to evidence‐based nursing implementation in mainland China: A qualitative content analysis. (23rd September 2020) - Fu, Yanfen; Wang, Chunqing; Hu, Yan; Muir‐Cochrane, Eimear
Abstract: It has been widely recognized that healthcare practices should be based on up‐to‐date high‐quality evidence; however, the implementation of evidence has been a slow process in nursing practice. It is crucial for clinical practitioners to be aware of the barriers to implementing evidence‐based nursing. The aim of this study was to describe participants' experiences and thoughts on barriers to implementing evidence‐based nursing in mainland China. Forty‐five participants came from 45 evidence‐based nursing implementation projects carried out in 16 hospitals in mainland China. Data were collected through observation and semi‐structured interviews, after which qualitative content analysis was undertaken. Then, the five themes and subthemes were extracted from the data. The five themes were evidence‐based, nurse‐related, patient‐related, setting barriers, and lack of support. In this study, a variety of barriers influencing evidence implementation in the Chinese nursing context were identified and further explored from the perspective of clarifying misunderstandings about evidence‐based nursing, the profound influence of Chinese culture on patients' preferences and attitudes, and the lack of professional knowledge of nurses.